Food Handler´s Perception of Fresh Cut Products - Barros, Manuela (2012)
The use of Fresh Cut Products (FCP) allows food service units to offer a greater variety of menus, reducing costs and minimizing cross contamination. Few food units in Portugal are adopting FCP, since these products are viewed as being more expensive and are regarded as less natural and easily perishable.The present study aims to identify and analyze the level of awareness of food service operators in respect to FCP. Approximately 90% of food handlers referred the use of FCP at their workplace, pointing as the main advantages for using them the less time spent on preparation (58.6%), the variety (55.9%) and the convenience (55.9%). Reasons for not using them were doubtful origin (91.7%), price (66.7%) and being a possible threat to their jobs (58.3%). In spite of recognizing the advantages of using FCP, most of food handlers (77.2%) prefer traditional products. Traditional products were preferred by food handlers with lower educational level, working at schools and performing functions of kitchen helper. FCP were chosen by younger food handlers, with higher educational level. It seems necessary to promote a demystification of this category of products near food service managers and employees, explaining the best way and advantages of using FCP at institutional food services in terms of safety, cost and quality.